Peningkatan Kesadaran Lingkungan di Sekolah Pedesaan - Kasim, Hermawaty Remba; Humairah; Asriani; Putri Arini; Hardi Hamid; Risna (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Environmental education plays a strategic role in changing human perceptions and attitudes towards environmental problems in the long term. early environmental education is very important in building a generation that cares and is responsible for the environment. This service aims to increase environmental awareness in rural schools through a socialization program involving lecturers as resource persons. Through this service program we managed to show a significant increase in environmental knowledge and awareness among students after attending the socialization program. Students showed positive behavioral changes such as throwing garbage in its place and participating in environmental conservation activities for example greening, and working together to clean their school environment. Keywords: Environmental Awareness; Cleanliness; Waste; Rural Schools Abstrak Pendidikan lingkungan berperan strategis dalam mengubah persepsi dan sikap manusia terhadap masalah lingkungan dalam jangka panjang. pendidikan lingkungan sejak dini sangat penting dalam membangun generasi yang peduli dan bertanggung jawab terhadap lingkungan. Pengabdian ini bertujuan untuk meningkatkan kesadaran lingkungan di sekolah-sekolah pedesaan melalui program sosialisasi yang melibatkan dosen sebagai narasumber. Melalui program pengabdian ini kami berhasil menunjukkan adanya peningkatan signifikan dalam pengetahuan dan kesadaran lingkungan di kalangan siswa setelah mengikuti program sosialisasi. Siswa menunjukkan perubahan perilaku yang positif seperti membuang sampah pada tempatnya dan berpartisipasi dalam kegiatan pelestarian lingkungan contohnya melakukan penghijauan, dan melakukan kerja sama membersihkan lingkungan sekolahnya. Kata Kunci: Kesadaran Lingkungan; Kebersihan; Sampah; Sekolah Pedesaan